Inhibition of EZH2 Ameliorates Lupus‐Like Disease in MRL/lpr Mice. Issue 10 (12th August 2019) - Rohraff, Dallas M.; He, Ye; Farkash, Evan A.; Schonfeld, Mark; Tsou, Pei‐Suen; Sawalha, Amr H.
Abstract : Objective: We previously identified a role for EZH2, a transcriptional regulator in inducing proinflammatory epigenetic changes in lupus CD4+ T cells. This study was undertaken to investigate whether inhibiting EZH2 ameliorates lupus‐like disease in MRL/ lpr mice. Methods: EZH2 expression levels in multiple cell types in lupus patients were evaluated using flow cytometry and messenger RNA expression data. Inhibition of EZH2 in MRL/ lpr mice was achieved by intraperitoneal 3′‐deazaneplanocin (DZNep) administration using a preventative and a therapeutic treatment model. Effects of DZNep on animal survival, anti–double‐stranded DNA (anti‐dsDNA) antibody production, proteinuria, renal histopathology, cytokine production, and T and B cell numbers and percentages were assessed. Results: EZH2 expression levels were increased in whole blood, neutrophils, monocytes, B cells, and CD4+ T cells in lupus patients. In MRL/ lpr mice, inhibition of EZH2 by DZNep was confirmed by significant reduction of EZH2 and H3K27me3 in splenocytes. Inhibiting EZH2 with DZNep treatment before or after disease onset improved survival and significantly reduced anti‐dsDNA antibody production. DZNep‐treated mice displayed a significant reduction in renal involvement, splenomegaly, and lymphadenopathy. Lymphoproliferation and numbers of double‐negative T cells were significantly reduced in DZNep‐treated mice. Concentrations of circulating cytokines and chemokines, including tumor necrosis factor, interferon‐γ, CCL2, RANTES/CCL5, interleukin‐10 (IL‐10), keratinocyte‐derived chemokine/CXCL1, IL‐12, IL‐12p40, and CCL4/macrophage inflammatory protein 1β, were decreased in DZNep‐treated mice. Conclusion: EZH2 is up‐regulated in multiple cell types in lupus patients. Therapeutic inhibition of EZH2 abrogates lupus‐like disease in MRL/ lpr mice, suggesting that EZH2 inhibitors may be repurposed as a novel therapeutic option for lupus patients.